Incidence of socioeconomic characteristics in student performance - Reading scale - Second grade of secondary school of basic education in the Census Evaluation of Students, by geographical area; year 2015 - Martín Efraín Mendoza Bolo (2019)
From a quantitative approximation, it is feasible to identify factors associated with the learning achievement of students not only from the educational institution. The student's environment must be considered. And in the student's environment, necessarily, the socio-economic stratum of the student's family is identified as an indicator. Socioeconomic characteristics will be described, according to geographic scope, from a socioeconomic index (elaborated by the Quality Measurement Unit) and Monetary Poverty (one-dimensional index collected by the National Institute of Statistics and Informatics) and will be investigated for its relationship with the performance of students in the secondary grade of secondary basic education. From the statistical methodology used, it follows that: (i) the highest percentage of monetary poverty in a region is associated with a higher percentage of students in the level of achievement prior to the beginning of the Reading scale. (ii) greater weighted average of a region in the Reading scale is associated with a higher socioeconomic index. (iii) what prevails, at the national level, is the distance-measurable-between urban and rural school performance.